Notes on vibration control of a micro/macromanipulator mounted on a flexible structure - Grandinetti, Francisco José [UNESP]; Soares, A. M. de S. [UNESP]; Lamas, W. de Q. [UNESP]; Goes, L. C. S. (Sage Publications Ltd, 2012)
The objective of this study is to describe the design and the implementation of an experimental set-up used to study the dynamics, the experimental identification, and the active vibration control of a flexible structure mounted manipulator system. The system consists of a three-degree-of-freedom cylindrical manipulator system with a flexible link on its tip. A two-degree-of-freedom polar rigid manipulator is mounted on the flexible macromanipulator. The dynamic modelling and experimental modal analysis identification in the frequency domain are being applied to design active digital control strategies for the micro-manipulator system to damp the mechanical vibrations of the flexible structure on the tip of the macro-manipulator system.
Keywords: flexible structure; micro/macromanipulator; modelling; robotics